Work and Family Disadvantage: Determinants of Gender Gaps in Paid Work During the COVID-19 Pandemic. (August 2022) - Mertehikian, Yasmin A.; Gonalons-Pons, Pilar
This article provides a comprehensive analysis of the increase in gender inequality in paid work during the pandemic to unpack the relative relevance of labor market and work-family conflict processes. Using panel data from the United States Current Population Survey, we examine four mechanisms in an integrated analysis that explicitly includes single-parent households and assesses the moderating role of women's economic position relative to their partners. The results indicate that increases in gender inequality during the pandemic were heavily concentrated in households with children but also partly connected to gender differences in prepandemic labor market positions and to the higher prevalence of women in lower earner position relative to their partners. Single parents were more negatively impacted than partnered parents, but the disproportionate concentration of this impact on women does not contribute much to increases in overall gender inequality due to the relatively smaller size of this group.